Socio-Economic Conditions of Fruits Seller Collectors in Ubung Kaja Village, North Denpasar Sub-district, Denpasar City - Mitha, NP Kanya; Widhianthini, Widhianthini; Rantau, Ketut (JURNAL MANAJEMEN AGRIBISNIS; Vol 8 No 2 (2020): OCTOBER 2020DO - 10.24843/JMA.2020.v08.i02.p03, 2020)
Socio-economic conditions of fruits seller collectors in Ubung Kaja village, North Denpasar sub-district, Denpasar City is a human position that is seen from the type of economic activity, income, education level, age, type of residence, and wealth owned. Fruits seller collectors in Ubung Kaja village, North Denpasar sub-district, Denpasar City is privately owned business that is not included in the market, while the market is regulated and developed by regional market companies. The gathering of fruits seller collectors in a location quite close to the market will cause competition between fruits seller and fruits seller collectors outside the market. The aim of this research are to analyze socio-economic conditions fruits seller collectors, economic, social dan institutional constraints, and strategies to resolve the constraints. Fruits seller collectors in this study include icome, initial capital, age, number of employees, and working hours. The research sample of 40 fruits seller collectors. The analysis technique used in this study are qualitative descriptive analysis and Interpretive Structural Modelling (ISM). The results of this study indicate that most traders are included in the category of small businesses and five of them are included in the micro business category with productive age and education level up to secondary school level. The element of constraints on micro business collectors who need attention is the income of fruits seller collectors. The strategy to resolve is marketing the fruit by online. The suggestions obtained from this research are for the government  is optimizing people’s business credit assistance and for the fruits seller collectors is better to keep inovating and developing business by utilizing social media.